ANALYSIS OF STUDENT PERSONALITY TYPES AND LECTURING MOTIVATION IN ACCOUNTING PROGRAM POLITEKNIK NEGERI MADIUN - Amri Amrulloh; La Ode Abdullah (Sean Institute, 2022)
This research aims to determine the personality types of students and the level of success of lecturers in motivating students. This research uses a descriptive method. The subjects in this study were students of the 4th semester of the Politeknik Negeri Madiun of Accounting Study Program with an age range of 19 years to 23 years. The data collection technique used is by distributing questionnaires. The total distribution of questionnaires is 115 questionnaires with a total of 94 questionnaires used. The data used in this study is primary data. The personality type of an accountant is described as ISFJ, INTJ, ESFJ, and ENTJ types. The results showed that the personality type of students when viewed from the average percentage of each respondent's questionnaire, students who had the ISFJ personality type were 9%, INTJ was 0%, ESFJ was 19%, and ENTJ was 1%. These results indicate that the personality of the students of the State Polytechnic of Madiun Accounting Study Program is not in accordance with the personality that an accountant should have. The results of the motivation questionnaire showed that the accounting lecturer at the Politeknik Negeri Madiun was enough to motivate students to become accountants